Kinerja Baznas Dalam Pendistribusian Dana Zakat, Infaq, Dan Shadaqah Melalui Program Hsu Makmur Di Kabupaten Hulu Sungai Utara - Riduan, Akhmad (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2021)
Islam which was revealed by Allah SWT to the Prophet Muhammad SAW not only contains teachings to build a relationship with Allah, but also relationships with fellow humans and other creatures of Allah. In relation to the humanitarian mission, it is known that Zakat, Infaq, and Sadaqah (ZIS) are managed by the people for the benefit of the people. The management of ZIS funds by Baznas as an extension of the government in Indonesia, especially in Hulu Sungai Utara Regency, is carried out based on five main programs, including the aim of empowering the people's economy through the HSU Makmur Program. With a qualitative approach, this study was conducted to describe the distribution of ZIS funds by Baznas Hulu Sungai Utara to the mustahiq where data were collected through observation techniques, purposive sampling interviews, and documentation studies. The data obtained were analyzed using data reduction, data display, and conclusion drawing/verification. The results of the study indicate that the productivity level of the HSU Makmur Program is low where the ZIS funds distributed have not been effective in encouraging the improvement of the mustahiq economic level, the quality of services provided is also not optimal. And although the preparation and development of the program is in line with the needs of the community, and even able to synergize with government policies so that it looks responsive and is considered accountable in the implementation of the HSU Makmur Program, the limitations of human resources have an impact on the low degree of responsibility that can be achieved. Therefore, Baznas Hulu Sungai Utara needs to coordinate with the Regional Government of Hulu Sungai Utara Regency as well as the ulama in order to confirm the existence and role of Baznas towards the wider community, especially muzakki so that more ZIS funds can be managed every year. Regarding the implementation of the HSU Makmur Program, Baznas should be able to synergize with related agencies so that the process of economic empowerment for mustahiq can take place more optimally, especially in terms of business assistance coupled with efforts to recruit human resources within the scope of Baznas itself.